Interactions due to moving heat sources in generalized thermoelastic half-space using L-S model - Sarkar, Nantu; Lahiri, Abhijit (Zielona Góra: Uniwersytet Zielonogórski)
A one-dimensional problem for a homogeneous, isotropic and thermoelastic half-space subjected to a moving plane of heat source on the boundary of the space, which is traction free, is considered in the context of Lord-Shulaman model (L-S model) of thermoelasticity. The Laplace transform and eigenvalue approach techniques are used to solve the resulting non-dimensional coupled equations. Numerical results for the temperature, thermal stress, and displacement distributions are represented graphically and discussed.
Keywords: generalized thrmoelasticity; L-S model; elastic half-space; moving heat sources; eigenvalue approach